2018 IEEE International Symposium on Workload Characterization (IISWC) 2018
DOI: 10.1109/iiswc.2018.8573503
|View full text |Cite
|
Sign up to set email alerts
|

Characterising Across-Stack Optimisations for Deep Convolutional Neural Networks

Abstract: Convolutional Neural Networks (CNNs) are extremely computationally demanding, presenting a large barrier to their deployment on resource-constrained devices. Since such systems are where some of their most useful applications lie (e.g. obstacle detection for mobile robots, vision-based medical assistive technology), significant bodies of work from both machine learning and systems communities have attempted to provide optimisations that will make CNNs available to edge devices. In this paper we unify the two v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Previous work shows that combining compression methods can achieve superior performance compared with using them in isolation, e.g., combining pruning and knowledge distillation [46]. The approach in [47] shows that distilling knowledge to shallower quantised architectures can achieve accuracy comparable with state-of-the-art full-precision models.…”
Section: Combining Knowledge Distillation With Quantisationmentioning
confidence: 99%
“…Previous work shows that combining compression methods can achieve superior performance compared with using them in isolation, e.g., combining pruning and knowledge distillation [46]. The approach in [47] shows that distilling knowledge to shallower quantised architectures can achieve accuracy comparable with state-of-the-art full-precision models.…”
Section: Combining Knowledge Distillation With Quantisationmentioning
confidence: 99%
“…In this paper, we propose grouped spatial pack convolutions (GSPC), for the common NCHW data layout 1 . We modify and extend the spatial pack convolutions (SPC) algorithm described in [11], which does not cover grouped convolutions.…”
Section: A Motivationmentioning
confidence: 99%
“…Figure 3 illustrates the GSPC algorithm with an example. We use tile sizes T O = T I = 2, as these are the maximum values allowed by the constraints (1). The initial data layout is shown on the left, with the channels split by group for clarity.…”
Section: B General Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNN benchmarking. Turner et al [57] implemented several common DNN compression techniques (weight pruning, channel pruning, and quantization) and evaluated the accuracy, execution time, and memory space on both CPU and GPU. They found that channel pruning can greatly reduce the execution time while weight pruning cannot.…”
Section: Related Workmentioning
confidence: 99%